Analysis of Factors Affecting Early Mobilization in Postoperative Patients After Lymphophymy Surgery in the Operating Room of Prof.Dr.H. Aloei Saboe Gorontalo City - Ade Anas Saputra; Fadly Syamsuddin; Asni Ayuba (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Background: Early mobilization is an important nursing intervention that plays a role in accelerating the patient's postoperative recovery. Lack of physical activity after surgery can increase the risk of complications, such as impaired circulation, decreased gastrointestinal function, as well as delayed wound healing. Therefore, early mobilization is an integral part of nursing care to maintain physiological function, improve comfort, and support the patient's rehabilitation process. This study aims to analyze the effect of early mobilization on postoperative patient recovery. Methods: The research method used was quantitative design with an observational analytical approach and using a cross sectional research design. A sample of 30 respondents was selected using the purposive sampling technique. Data was collected through an early mobilization observation sheet. Data analysis was conducted using the Chi-Square test to identify the effect of early mobilization on the patient's postoperative recovery. Results: The results of the study showed the effect of early mobilization on the recovery of postoperative patients with a significance value of p < 0.05. Patients who received early mobilization showed improvement in clinical conditions compared to before the intervention. Discussion: Early mobilization contributes to improving blood circulation, improving organ function, and preventing postoperative complications. Gradual physical activity helps speed up healing and increase patient independence. These findings confirm the importance of the role of nurses in encouraging early mobilization as an effective strategy to improve patient clinical outcomes.